Fermentation characteristics of lactofermented cucumbers using an isolated Lactiplantibacillus plantarum NCHU–FC1 strain - Hsuan-Min Wang; Shwu-Jene Tsai; Jin-Yuarn Lin (Applied Food Research)
A lactic acid bacteria (LAB) strain in naturally developed lactofermented cucumbers was isolated, identified, and subjected to co-fermenting cucumbers in this study. Changes in pH values, total nitrite contents, total plate count, total LAB counts, and microbial composition were monitored. The isolated LAB strain was identified as a Lactiplantibacillus (Lpb.) plantarum strain coding as Lpb. plantarum NCHU–FC1. The pH value was quickly lower than 4.6 (aka high-acid foods), while total nitrite contents were below the standard limit using 1 × 107 colony forming unit (CFU)/mL Lpb. plantarum NCHU–FC1 at 4 °C for 5 days. The increase in total plate count (TPC) was slow in the isolated LAB-fermented cucumbers. Consequently, 1 × 107 CFU/mL Lpb. plantarum NCHU–FC1 at 4 °C for 5 days was suggested as an optimal culture condition for developing this LAB co-fermented cucumber. At the optimal culture condition, percentages of Lpb. plantarum NCHU–FC1 in 0-day and 5-day co-fermented cucumbers were 97.50% and 98.60%, respectively. Our results evidence the fermentation safety, stability, and dominance of the isolated Lpb. plantarum NCHU–FC1 strain for developing a single LAB co-fermented cucumbers. The isolated Lpb. plantarum NCHU–FC1 strain has been characterized and may be further applied in the nutraceutical, pharmaceutical, and food industries.